Developing a controlled traffic (tramline) farming system - Kuvachov, Volodymyr; Кувачов, Володимир Петрович (НУБІП України, 2024)
Intensification of agricultural production. products in the world, led to the fact that the energy security and energy availability of rural areas production has increased several times in recent years. Due to this, the problem of overcompaction of soils by the running systems of heavy tractors and agricultural machinery has become the most relevant and urgent in almost the entire world. machines, which caused "machine degradation of soils" and, as a result, a decrease in their fertility and yield of crops. At the same time, from over-compaction of the soil by running systems of rural and urban areas. equipment, soil resistance also increases, which increases energy consumption in agriculture. To preserve and restore soil fertility, as well as to realize the potential biological yield of cultivated plants, it is necessary to learn how to grow plants without destroying and compacting the soil. The most progressive and promising way of growing plants without destroying and compacting the soil is Controlled Traffic Farming (CTF).
Keywords: farming system; machine degradation